Hubungan Indeks Massa Tubuh dengan Kadar Gula Darah pada Pasien Diabetes Melitus di Puskesmas Bongo Ii Kabupaten Boalemo - Sukmawaty Sukmawaty; Aloysia Ispriantari (CV. ALIM'SPUBLISHING, 2026)
Diabetes mellitus, as a persistent non-infectious metabolic pathology increasingly prominent in the global epidemiological spectrum, is fundamentally characterized by dysfunctional hyperglycemia rooted in primary disruptions of pancreatic insulin hormone synthesis or peripheral resistance to its biological action, thereby inducing dynamic imbalances in gluconeogenesis and glycolysis pathways; amid the hypothesis that body mass index (BMI) as a measure of central adiposity potentially mediates variability in serum glucose levels, this quantitative observational study with a cross-sectional design rigorously tests the causal relationship between BMI and fasting/random blood glucose concentrations in a cohort of 134 adult subjects with type 2 diabetes mellitus affiliated with primary care services at Puskesmas Bongo II, Boalemo Regency, through an inclusive total sampling recruitment strategy, precision anthropometric measurement instruments (height, weight, WHO BMI categorization), and laboratory-validated glucometric validation, with multivariate inferential processing based on the Chi-Square independence test at a Type I error rate of α=0.05 using the latest edition of the SPSS analytical suite; the demographic profile highlights female gender supremacy (90 individuals, 67.2%), the normoweight group (78 cases, 58.2%), concurrent with substantial glycemic elevation prevalence (78 subjects, 58.2%), but the crucial statistical output reveals a p-value of 0.831 (>0.05) that negates any probabilistically meaningful association, thus the substantive conclusion affirms the non-significance of the BMI-glucose relationship in this local context, while implying the dominance of alternative etiopathogenic factors such as hypercaloric macronutrient intake patterns, deficits in aerobic/anaerobic physical activity, non-adherence to multidisciplinary pharmacological protocols (e.g., metformin/oral hypoglycemics), and a comprehensive management paradigm integrating behavioral education, continuous monitoring, and personalized interventions to mitigate long-term cardiovascular risks across the diabetes mellitus spectrum.